Missing analyst forecasts and corporate fraud: evidence from China - Ren, Liuyang (Journal of business ethics, 2022)
The relationship between analysts' forecasts and corporate fraud is a vital theoretical and practical question that needs to be clarified. Based on a strict distinction between negative performance gaps relative to analyst forecasts (negative forecast gaps hereinafter) and analyst coverage, this study investigates the influence of analyst forecasts on corporate fraud from a panoramic perspective. Using panel data on listed companies in China from 2008 to 2019, we find that short-term performance pressure caused by negative forecast gaps is significantly positively correlated with firms’ possibility for fraudulent behavior. However, this positive correlation is weaker in state-owned enterprises than in their non-state-owned counterparts. Further, as a key external governance mechanism, analyst coverage enhances the negative moderator effect of state ownership on the positive relationship between negative forecast gaps and the likelihood of corporate fraud.